TANTANGAN SISTEM NOKEN DI PAPUA PEGUNUNGAN DALAM PERSPEKTIF ILMU SOSIAL DAN BUDAYA - Maya Andryani (Fakultas Hukum Universitas Kristen Indonesia, 2026)
General elections in the Papua Mountains region are known to use the noken system. The Noken system is a typical Papuan voting method based on customary deliberation, in which tribal chiefs or community leaders represent the community to cast votes, often using traditional